Қазіргі қазақ психологиялық драмасы З.Шашкиннің «Ақын жүрегі» пьесасы бойынша - Кішкенбаева, Ж.Қ. (ҚарМУ баспасы, 2010)
Автор, опираясь на мировой литературоведческий опыт, выявляет основные закономерности казахской психологической драмы, а также историю традиций в этом жанре. В статье рассматриваются вопросы возникновения, развития казахской психологической драмы и проблемы характера и конфликта в психологической драме на материале пьесы З.Шашкина «Сердце поэта». The author of article, leaning on world study of literature experience, reveals the basic laws of the Kazakh psychological drama, and also history of traditions in this genre. In article questions of origination, development of the Kazakh psychological drama, and a problem of character and the conflict in a psychological drama on a material of the play of Z.Shashkin «Heart of the Poet» are considered.
Keywords: драматургия; Қазіргі қазақ психологиялық драмасы; З.Шашкин; «Ақын жүрегі» пьесасы